Editors, librarians, and publication exchange: The Royal Swedish Academy of Sciences in the long 19th century. (6th April 2020) - Beckman, Jenny
Abstract: The paper discusses the publications of the Royal Swedish Academy of Sciences (RSAS) as part of a wider network of publication exchange, linking learned societies, libraries, and archives. The periodicals of the RSAS went through several reorganisations between 1813 and 1903, all to some extent related to their role in publication exchange. Although subject to many of the same deliberations of commercial value and institutional prestige as the expanding book trade, publication exchange offered a means of communication for institutions with widely differing financial, linguistic and scientific status, and a forum for articulating a wide range of values significant in scientific publication. In the context of publication exchange, the roles of producers and consumers, and of publishers and repositories of scientific knowledge overlap, and librarians emerge alongside editors as central actors in scientific communication. Scientific editorship should be viewed not only as a means of disseminating scientific findings to wider audiences, but as designing a product that could be used to forge institutional connections, to acquire publications, and to build collections. The case of the RSAS periodicals highlights the importance of publication, not only for the distribution of scientific knowledge, but for its acquisition.